การพัฒนาระบบเฝ้าสังเกตสำหรับสถานีวัดอากาศแบบเคลื่อนที่ - วัจนเทพินทร์ นภัทร; สมบูรณ์กิจ ปกรณ์ (RMUTP Research Journal Sciences and Technology, 2014)
The objective of this research was to develop a high performance monitoring software for extended database of mobile weather station by using embedded computer. The monitoring system could measure and record temperature, relative humidity, wind speed and direction, rainfall, solar radiation and UV index. The software could convert these parameters and sent them from mobile unit to base unit within 60meters distance via 868.0MHz of radio frequency. The embedded computer was used as for database and host of the monitoring software. This software was developed by using LabVIEW with large MySQL database.The software could work perfectly. That is, it could monitor and display any parameter in real time in both graphic and numerical data. It could also produce a report in correct format of research information. The Monitor system could work with the embedded computer. The mobile weather station could be used in remote areas with photovoltaic energy system and storage battery specially designed for them.